2011
DOI: 10.1093/ndt/gfr003
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the CKD-EPI equation to estimate glomerular filtration rate in a Caucasian population

Abstract: In comparison with the MDRD(4) formula, the CKD-EPI equation leads to higher estimates of GFR in young people and lower estimates in the elderly. On a population level, this may lead to higher estimates of kidney function. However, in routine clinical practice where the population is predominantly elderly, the opposite may be true. The introduction of eGFR(CKD-EPI) necessitates reconsidering the definition of CKD. We suggest introducing age-dependent threshold values and/or the use of urinary albumin excretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 19 publications
10
56
0
4
Order By: Relevance
“…Fan et al reported that the CKD-EPI equation has slight (but nonsignificant) overestimation of GFR in women in this population compared with men, which would have led to a lower lifetime risk of CKD, not higher as was observed (25). Finally, most other studies that use eGFR to ascertain CKD or establish reference values for GFR in the general population, including studies from Iceland, have also shown higher prevalence of CKD or lower levels of GFR in women (14,15,24,26,27). In our study, women had an eGFR that was approximately 5 ml/min per 1.73 m 2 lower than men at baseline.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Fan et al reported that the CKD-EPI equation has slight (but nonsignificant) overestimation of GFR in women in this population compared with men, which would have led to a lower lifetime risk of CKD, not higher as was observed (25). Finally, most other studies that use eGFR to ascertain CKD or establish reference values for GFR in the general population, including studies from Iceland, have also shown higher prevalence of CKD or lower levels of GFR in women (14,15,24,26,27). In our study, women had an eGFR that was approximately 5 ml/min per 1.73 m 2 lower than men at baseline.…”
Section: Discussionmentioning
confidence: 76%
“…The difference may be attributable to faster progression to ESRD in men, increased survival in women, inaccuracies in estimating equations, or lower levels of normal GFR in women. In support of the first factor, some studies (23), although not all (24), have shown a lower prevalence of albuminuria associated with low eGFR in women than men. Our data do not show significant differences in lifetime risk of stage 4 CKD between men and women.…”
Section: Discussionmentioning
confidence: 89%
“…9 -12,16 -18 However, the present data are consistent with a recent report from the Nijmegen Biomedical Study, which found that the CKD-EPI formula provided lower values of eGFR than the MDRD formula in older subjects. 19 Thus, impaired renal function is even more common in HF than previously appreciated. Indeed, the present study may even have underestimated the prevalence of renal dysfunction because we did not have data on albuminuria, cystatin C, or rate of decline in eGFR, all of which are indicators of renal dysfunction that may not be apparent in patients with eGFR still in the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…La problé matique de l'estimation du DFG chez le sujet âgé de plus de 70 ans est bien entendu d'une importance capitale vu le pourcentage que repré sentent ces patients dans la pratique mé dicale d'une part, et le pourcentage de ces patients avec un DFG diminué d'autre part (que cette diminution soit physiologique ou pathologique) [22,95,96]. Il faut remarquer que les sujets âgé s de plus de 70 ans repré sentaient une minorité des patients des cohortes de dé veloppement des é quations Cockcroft, MDRD et CKD-EPI.…”
Section: La Problé Matique Du Sujet âGéunclassified